Understanding the Effects of Ethylene as an Airborne Contaminant in Proton Exchange Membrane Fuel Cells and its Mitigation via Filtration - Mahmoud Amirsalehi; Connor Miles; Justin Jordan; Karen E. Swider‐Lyons; William Earl Mustain (ChemElectroChem)
Proton exchange membrane fuel cells (PEMFCs) are a promising clean energy technology, but their performance and durability are highly sensitive to contaminants in both the fuel and oxidant streams. Among these, ethylene (C2H4) is of particular interest due to its presence in industrial and warehouse environments. This study investigates the impact of ethylene contamination on PEMFC performance when introduced into the cathode air feed. A combination of fuel cell performance testing, cyclic voltammetry, and gas chromatography is used to analyze the interaction of ethylene with the cathode catalyst. The presence of 20–300 ppm ethylene in air causes an immediate drop in the fuel cell operating voltage that is quickly recovered once the contaminant is removed, suggesting a reversible adsorption mechanism on the surface of the platinum cathode electrocatalyst, rather than the formation of strongly bound oxidation intermediates. Additionally, the study explores mitigation strategies by evaluating conventional and chemically modified air filters. While commercial air filters prove ineffective, a carbon supported platinum (Pt/Vulcan)‐coated filter demonstrates partial ethylene removal, reducing performance losses. These findings provide critical insights into ethylene contamination mechanisms and offer potential mitigation strategies to improve PEMFC reliability in real‐world applications.